Multi-wavelength focusing based on nanoholes. (17th July 2020) - Han, Yuansheng; Lu, Xiaoqing; Lv, Haoran; Mou, Zhen; Zhou, Changda; Wang, Shuyun; Teng, Shuyun
Abstract: A kind of controllable multi-wavelength focusing metalenses is proposed. The proposed metalenses consist of identical nanometer holes etched in silver film and the beam focusing at three primary wavelengths is controlled without additional phase compensation. Transmission field of metalens satisfies the in-phase interference condition at different wavelength and the fixed focal effect for three primary wavelengths and the color separation along the transverse or longitudinal direction are realized respectively. Simulation and experimental results verify the controllable focusing performance of the proposed metalenses. Simple design, convenient manufacture and effective color controllable focusing of these proposed metalenses are helpful for the applications of metalenses in lightweight chromatically-corrected displaying and imaging systems.